LINGVISTIK TADQIQOTLARDA KIYIM-KECHAKNI ANGLATUVCHI LEKSIKANING O‘ZIGA XOS XUSUSIYATLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article is devoted to the study of the specific features of the vocabulary representing clothing. The study covers the cultural, historical, spiritual, and social aspects of the composition of this dictionary, as well as its gender and social determination.
Keywords: Linguistics, lexicon, language, clothing, semantics, culture, costume, national culture.